Qualitative Research and the Academy of Management Journal - Gephart, Robert P. (Academy of Management Journal, 2004)
Robert Gephart from the University of Alberta reflects on his observations as a long-serving, award-winning reviewer of qualitative research for this journal. Despite many successes, most qualitative papers do not succeed in being accepted. This situation is not surprising for a journal with a 10% acceptance rate. However, it seems that there are certain recurrent issues in qualitative submissions that, if addressed, could improve the prospects for positive revise and resubmit decisions and ultimate acceptance at this journal. Qualitative research required qualitative methods by definition. It is important to show what was done in the research process and to articulate how research practices transformed observations into data, results, findings, and insights. The methodology used need not be complex, and the methodological account need not dominate the written report. The author also outlines common problems and challenges found in many qualitative submission to this journal and potential solutions to these problems.